Su alcune occorrenze di ὀρέγω - Dettori, Emanuele (Hyperboreus, 2019)
Three of the contexts in which ὀρέγω ‘to hand out’ is used with a deﬁnite object are: (1) ‘to hand out a cup (on a convivial occasion)’; (2) ‘to give food and drink to those in need’; (3) ‘to offer a gift’. Starting from these uses, it is possible to see the meaningfulness of some occurrences of the verb and to interpret others in more detail than has previously been done.